Risk of poor glycemic control in tamsulosin versus finasteride users with type 2 diabetes mellitus - Minh-Ha Nguyen; Maxim S. Petrov; Jaelim Cho (Heliyon)
Background: Benign prostatic hyperplasia (BPH) is strongly related to type 2 diabetes. Recent evidence has been inconsistent regarding the effect of BPH medications on glucose homeostasis. This study examined the risk of poor glycemic control associated with finasteride and tamsulosin use in individuals with type 2 diabetes. Methods: We conducted a retrospective cohort study with a new-user, active-comparator design, utilizing nationwide pharmaceutical dispensing and hospitalization databases in New Zealand. The study cohort consisted of men with type 2 diabetes who were prescribed finasteride (n = 1,259) or tamsulosin (n = 580). Inverse probability treatment weighting using propensity scores was applied to create a weighted population with balanced baseline covariates. Cox proportional hazard models were fitted to estimate the risk. Results: During a median follow-up of 2.4 years for finasteride users and 1.6 years for tamsulosin users, the incidence rates were 564 per 10,000 person-years and 409 per 10,000 person-years in tamsulosin users and finasteride users, respectively. After applying inverse probability treatment weighting, tamsulosin users did not have a significantly higher risk of poor glycemic control compared with finasteride users (weighted hazard ratio 1.27, 95 % confidence interval 0.95–1.72). Sensitivity analyses addressing confounding and protopathic bias yielded similar risk estimates. Conclusions: We found that there was a non-differential risk of poor glycemic control between tamsulosin users and finasteride users during long-term use.